Synthesis, structural characterization, and hydrolysis of Ammonia Borane (NH3BH3) as a hydrogen storage carrier - Figen, Aysel Kanturk; Piskin, Mehmet Burcin; Coskuner, Bilge; Imamoglu, Verda (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
In the present study, synthesis, structural characterization, and hydrolysis of the promising hydrogen storage carrier ammonia borane (NH3BH3), were investigated. NH3BH3 was prepared by one-pot chemical reaction between sodium borohydride (NaBH4) and different ammonia salts [NH4X, X: SO4, CO3, Cl] in the presence of solvent, tetrahydrofurane (THF). Synthesizes with different temperatures (20-40 degrees C), reaction times (30-130 min), amount of added THF volume (50-200 ml) and NaBH4/(NH4)(2)SO4 input molar ratios (0.47-0.75) were performed in order to find the optimum reaction conditions for obtaining maximum product yield. The characterization of NH3BH3 products was carried out by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), Raman spectroscopy (RS), elemental analysis (C, H, N, O) and NMR spectroscopy. Characterization results indicated that NH3BH3 as a crystalline powder at 98% purity was achieved with 92.18% production yield. Additionally, hydrolysis of product NH3BH3 in the presence of amorphous Co-B catalyst at 22-80 degrees C under magnetic stirring (700 rpm) was performed. The maximum hydrogen generation rate was 5447.80 ml min(-1) g cat(-1) and the hydrolysis reaction kinetics were clarified based on zero-order, first-order and Langmuir-Hinshelwood kinetic models. Copyright (c) 2013, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Ammonia Borane; Synthesis; Structural characterization; Hydrolysis; Kinetics; GENERATION; DEHYDROGENATION; CATALYSTS; RELEASE; SODIUM; Chemistry; Electrochemistry; Energy & Fuels